Existence of a true phosphofructokinase in Bacillus sphaericus: Cloning and sequencing of the pfk gene - Alice, A.F. (2002)
Some strains of Bacillus sphaericus are entomopathogenic to mosquito larvae, which transmit diseases, such as filariasis and malaria, affecting millions of people worldwide. This species is unable to use hexoses and pentoses as unique carbon sources, which was proposed to be due to the lack of glycolytic enzymes, such as 6-phosphofructokinase (PFK). In this study, PFK activity was detected and the pfk gene was cloned and sequenced. Furthermore, this gene was shown to be present in strains belonging to all the homology groups of this heterogeneous species, in which PFK activity was also detected. A careful sequence analysis revealed the conservation of different catalytic and regulatory residues, as well as the enzyme's phylogenetic affiliation with the family of allosteric ATP-PFK enzymes.